2014
DOI: 10.5194/gmdd-7-6629-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hindcast regional climate simulations within EURO-CORDEX: evaluation of a WRF multi-physics ensemble

Abstract: Abstract. In the current work we present six hindcast Weather Research and Forecasting (WRF) simulations for the EURO-CORDEX domain with different configurations in microphysics, convection and radiation for the time period 1990–2008. All regional model simulations are forced by the ERA-Interim reanalysis and have the same spatial resolution (0.44°). These simulations are evaluated for surface temperature, precipitation, short- and longwave downward radiation at the surface and total cloud cover. The analysis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 39 publications
7
45
0
3
Order By: Relevance
“…[] and Katragkou et al . []. In addition to these main settings, the models also differ, e.g., in the configuration of the lateral boundary relaxation zone around the EURO‐CORDEX focus domain, the number of vertical levels, or interpolation settings for initial and static fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[] and Katragkou et al . []. In addition to these main settings, the models also differ, e.g., in the configuration of the lateral boundary relaxation zone around the EURO‐CORDEX focus domain, the number of vertical levels, or interpolation settings for initial and static fields.…”
Section: Methodsmentioning
confidence: 99%
“…For the subset of WRF simulations within the EURO‐CORDEX ensemble Katragkou et al . [] evaluated shortwave and longwave radiation and cloud cover and their relation to temperature and precipitation biases. In an evaluation study on the added value of increased spatial resolution on the reproduction of precipitation extremes, Prein et al .…”
Section: Introductionmentioning
confidence: 99%
“…Both use WSM-5 microphysics (Hong et al 2004), RRTMG radiation (Iacono et al 2008), the YSU PBL scheme (Hong et al 2006) and the NOAH land surface model (Ek et al 2003). This choice of setup results from several validation studies of WRF Euro-CORDEX evaluation simulations (Kotlarski et al 2014;García-Díez et al 2015;Katragkou et al 2014). Since the 3 km domain is directly nested into the EUR-11 domain, both simulation types share the same boundary conditions for Central Europe.…”
Section: Rcm Simulationsmentioning
confidence: 99%
“…The model performance for meteorology affects both the air quality results and the calculated emissions. Several studies focused on all of Europe and reported biases for both air temperature and precipitation (Miglietta et al [37], Katragkou et al [38], Wałaszek et al [39], Kim et al [40], and Warrach-Sagi et al [41]). Recent findings provided by Skjøth et al [42] show that the bias in air temperature at 2 m varies spatially and seasonally.…”
Section: The Wrf-chem Modelmentioning
confidence: 99%